Local Reference Ranges of Thyroid Volume in Sudanese Normal Subjects Using Ultrasound. (26th September 2011) - Yousef, Mohamed; Sulieman, Abdelmoneim; Ahmed, Bushra; Abdella, Alsafi; Eltom, Khaled
Abstract : This study aimed to establish a local reference of thyroid volume in Sudanese normal subjects using ultrasound. A total of 103 healthy subjects were studied, 28 (27.18%) females and 75 (72.82%) males. Thyroid volume was estimated using ellipsoid formula . The mean age and range of the subjects was 21.8 (19–29) years; the mean body mass index (BMI) was 22.3 (16.46–26.07) kg/m 2 . The overall mean volume ± SD volume of the thyroid gland for both lobes in all the patients studied was 6.44 ± 2.44 mL. The mean volume for both lobes in females and males were 5.78 ± 1.96 mL and 6.69 ± 2.56 mL, respectively. The males' thyroid volume was greater than the females'. The mean volume of the right and left lobes of the thyroid gland in males and females were 3.38 ± 1.37 mL and 3.09 ± 1.24 mL, respectively. The right thyroid lobe volume was greater than the left. The values obtained in this study were lower than those reported from previous studies.